Implementasi Metode Amtsilati Dalam Meningkatkan Kemampuan Maharah Qiro'ah - Ach. Sholehuddin; Mualim Wijaya (Institut Agama Islam Negeri Curup, 2019)
This study presents the Implementation of the Amtsilati Method in Improving the Ability of Maharah Qiro'ah at the Amtsilati hostel in K Pondok Pesantren Nurul Jadid, Paiton, Probolinggo area. The purpose of this study was to describe how the Amtsilati method was implemented in improving Maharoh Qiro'ah's skills in the Amtsilati K Pondok'Pesantren Nurul Jadid area. This research is a descriptive study with a qualitative approach. The subjects in this study include educators, dormitory managers and students. Data collection techniques used were interviews, observation and documentation. The collected data is analyzed through several stages: display data, data reduction and conclusion. And the results of this study indicate that the Application of the Amtsilati Method in the Amtsilati dormitory of K Pondok'Pesantren Nurul Jadid Area was able to improve the skill of Maharah Qiro'ah. The application of the Amtsilati method is in line with its application, except that there is little difference with the application of Amtsilati at its center Darul Falah Islamic Boarding School, Jepara. The learning process with the Amtsilati Method in Pesantren Nurul Jadid begins with reading khulashoh, hadloroh, qoidah then explanation, exposure to some examples, synchronization and evaluation